Rheological and adhesive properties of PIB-based pressure-sensitive adhesives with montmorillonite-type nanofillers. (March 2016) - Brantseva, Tatiana; Antonov, Sergey; Kostyuk, Anna; Ignatenko, Viktoria; Smirnova, Nina; Korolev, Yurii; Tereshin, Alexey; Ilyin, Sergey
Abstract : Graphical abstract: Highlights: Clay nanofillers are used to enhance shear resistance of non-crosslinked PSAs. Validity of Chang's viscoelastic windows is tested for such PSAs with nanofillers. Rheological properties propose structure best appropriate for high shear resistance. Cloisite 15A & silica enable 2–4 orders of magnitude growth in PIB PSA holding time. Abstract: Two clays (natural unmodified Cloisite Na + and organomodified Cloisite 15A) were used to suppress cold flow of polyisobutylene (PIB)-based adhesives. In accordance with the results of rheological measurements two types of structure in the systems studied were suggested: presence of the rigid and fragile clay aggregates in a viscoelastic matrix with no intercalation in case of unmodified clay and partially-intercalated system with the clay particles connected into a joint network by the polymer molecules adsorbed on their surface for organomodified clay. SEM and XRD data confirm partial intercalation in PIB-Cloisite 15A adhesives, as well as aggregation and no intercalation in PIB-Cloisite Na + adhesives. A notable change in the structure in PIB-40 wt.% Cloisite 15A system, leading to elastic properties prevailing, allowed a huge increase in the holding time for these formulations – up to 3–4 orders of magnitude. Clay usage allowed also obtaining an increase in peel resistance in the systems, from ∼10% up to twofold values – depending on the type and content of the clay used. It was accompanied however by some decrease in tack properties of the formulations because of the deteriorated conditions of adhesion joint formation (higher viscosity) due to the clay incorporation.